Multi-collector ICP-mass spectrometry reveals changes in the serum Mg isotopic composition in diabetes type I patients. Issue 7 (11th June 2019) - Grigoryan, Rosa; Costas-Rodríguez, Marta; Van Laecke, Steven; Speeckaert, Marijn; Lapauw, Bruno; Vanhaecke, Frank
Abstract : Serum Mg shows a lighter isotopic composition in diabetes type-1 patients than in an age- and gender-matched reference population. Abstract : Magnesium is an essential mineral element in the human body, playing a crucial role in the carbohydrate metabolism and insulin action. Mg deficiency has been shown to be associated with diabetes type 1 (T1D) and type 2 (T2D). However, the total serum Mg concentration does not adequately reflect the individual Mg status as a reduced intracellular or ionized serum Mg concentration, i.e. the physiologically active serum fraction, can occur despite a normal Mg serum concentration. Therefore, we explored the isotopic composition of serum Mg as an alternative parameter. A method for Mg isotopic analysis of serum via multi-collector inductively coupled plasma-mass spectrometry (MC-ICP-MS) after acid digestion and isolation of Mg from the concomitant matrix using AG50W-X8 strong cation exchange resin was optimized. Several reference materials of biological and geological origin were included for validation purposes. Mg isotope ratios were expressed relative to both the DSM3 isotopic reference material and ERM-AE143, as an alternative/new isotopic standard. Subsequently, the serum Mg isotopic composition was investigated in patients with T1D and compared to that in healthy individuals (reference population). Patients were re-evaluated after one year. The Mg isotopic composition was significantly lighter for the T1D patients than for the reference population and after one year, a similar shift in the average δ Mg value was observed. However, for some of the T1D patients, a statistically significant difference was established between the δ Mg values corresponding to the two sampling events. This variability could be related to the effect of administered insulin on the transcellular kinetics of Mg, inherent characteristics of the T1D patients, such as variable glycemic control, and/or differences in the Mg isotope fractionation accompanying intestinal uptake and/or renal excretion and/or in the distribution of Mg isotopes across body compartments. Further research is required to identify the governing factor(s).